2006
DOI: 10.1038/nature05322
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of seismogenic volcanic extrusion at Mount St Helens in 2004–05

Abstract: The 2004-05 eruption of Mount St Helens exhibited sustained, near-equilibrium behaviour characterized by relatively steady extrusion of a solid dacite plug and nearly periodic shallow earthquakes. Here we present a diverse data set to support our hypothesis that these earthquakes resulted from stick-slip motion along the margins of the plug as it was forced incrementally upwards by ascending, solidifying, gas-poor magma. We formalize this hypothesis with a dynamical model that reveals a strong analogy between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
1
9

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 199 publications
(201 citation statements)
references
References 24 publications
6
185
1
9
Order By: Relevance
“…As noted by Iverson et al [2006], the 2004-2008 eruption of Mount St. Helens also offers an exceptional opportunity to link shallow volcanic seismicity with extrusion dynamics. However, the bulk of such analysis is beyond the scope of this paper, and here we summarize only key observations with the caveat that some of these observations may be superseded by future work.…”
Section: Association With Seismicitymentioning
confidence: 99%
See 3 more Smart Citations
“…As noted by Iverson et al [2006], the 2004-2008 eruption of Mount St. Helens also offers an exceptional opportunity to link shallow volcanic seismicity with extrusion dynamics. However, the bulk of such analysis is beyond the scope of this paper, and here we summarize only key observations with the caveat that some of these observations may be superseded by future work.…”
Section: Association With Seismicitymentioning
confidence: 99%
“…Hybrid earthquakes were interpreted by Harrington and Brodsky [2007] as brittle failure events involving low rupture velocities and strong path effects. Iverson et al [2006] modeled the drumbeat events as caused by repeating slip on the margin of the ascending magma plug. Waite et al [2008] however, analyzed long-period seismic events recorded during the summer of 2005, and concluded that these events were inconsistent with a shear-faulting source and suggested instead the repetitive opening and closing of a steam-or fluid-filled crack or cracks located beneath the growing lava dome.…”
Section: The 2004-2008 Eruption Of Mount St Helensmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrologic and geodetic modeling studies suggest that the 2004-2008 eruption was fueled by a magma source about 5 kilometers deep; apparently, old thoroughly degassed magma moved to the surface in the more recent eruptions from this depth without significant recharge of fresh magma. The triggering mechanism for such an eruption remains enigmatic, but a model describing forces driving and resisting dome extrusion implies a balance between magma pressure and friction so delicate that even slight changes could have altered the eruption character [Iverson et al, 2006].…”
Section: Reawakeningmentioning
confidence: 99%